2019
DOI: 10.1080/87559129.2019.1696359
|View full text |Cite
|
Sign up to set email alerts
|

Edible Bird’s Nest: Physicochemical Properties, Production, and Application of Bioactive Extracts and Glycopeptides

Abstract: Edible bird's nest (EBN), the swiftlet's nest, has been consumed for centuries as a tonic or health food. The information upon the usage and benefits of the EBN are largely based on historical and observational reports since its discovery, until some were proven scientifically at recent times. Studies have been conducted on the major components of the EBN, i.e. glycoprotein, in attempts to elucidate the roles of the glycoprotein in terms of functionality toward health improvement. This article presents a revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 73 publications
0
21
0
4
Order By: Relevance
“…TCM claimed that EBN can treat malnutrition, improve metabolism rate, boost immune system and rejuvenate the skin complexion ( Bashir et al, 2017 ). Moreover, in the modern research, EBN also exhibits some interesting therapeutic effects, such as anticancer, anti-aging, phlegm-dissolving, cough-suppressing, anti-tuberculosis, voice-improving, curing general debility and asthenia, and hastening recovery from illness and surgery ( Daud et al, 2019a ). There is a great amount of research taking place on the investigation of the hidden nutritive and pharmacological properties of EBN.…”
Section: Introductionmentioning
confidence: 99%
“…TCM claimed that EBN can treat malnutrition, improve metabolism rate, boost immune system and rejuvenate the skin complexion ( Bashir et al, 2017 ). Moreover, in the modern research, EBN also exhibits some interesting therapeutic effects, such as anticancer, anti-aging, phlegm-dissolving, cough-suppressing, anti-tuberculosis, voice-improving, curing general debility and asthenia, and hastening recovery from illness and surgery ( Daud et al, 2019a ). There is a great amount of research taking place on the investigation of the hidden nutritive and pharmacological properties of EBN.…”
Section: Introductionmentioning
confidence: 99%
“…In traditional Chinese medicine, EBNs are prescribed to treat diseases such as tuberculosis, asthma, dry cough, hemoptysis, asthenia, difficulty in breathing, gastric troubles, and general bronchial ailments [3]. Interestingly, EBNs have also been the focus of modern research and technology, which have revealed their nutritional value and pharmacological activities, including anti-aging, anti-cancer, cough-suppressing, anti-tuberculosis, voice-improving, and phlegm-dissolving properties [4]. Meanwhile, in the food industry, EBN extract has been used as one of the ingredients in foods, drinks, and nutraceutical products.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, in the food industry, EBN extract has been used as one of the ingredients in foods, drinks, and nutraceutical products. For example, ice cream with 0.2% EBN extract was found to be more favorable than the others due to high melting rates and lower sweetness [4]. These positive nutritional and health effects have increased the demand and supply of EBNs and have generated increasing interest among researchers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nests are built during breeding season and are made almost entirely from saliva that contain glutinous material produced by the bird's sublingual salivary glands [17][18][19][20][21]. It is produced by several different swiftlet species in the genus of Aerodramus and Collocolia and the nest is mainly built by male swiftlets [22].…”
Section: Introductionmentioning
confidence: 99%